Regulation of Nitrate Reductase in Excised Barley Roots - Smith, F. W. (1971)
When excised barley roots (Hordeum distichum L.) are appropriately pretreated, the level of nitrate reductase in the roots increases upon exposure to nitrate. Relatively low levels of nitrate (10 μm) gave maximum induction of nitrate reductase. This increase was inhibited by inhibitors of protein and RNA synthesis, indicating that de novo protein synthesis is probably involved. Induction of nitrate reductase by nitrate is partially prevented by the inclusion of ammonium, an eventual product of nitrate reduction, in the incubation medium. Under the experimental conditions used, ammonium did not inhibit the uptake of nitrate by excised barley roots. It is concluded, therefore, that ammonium, or a product of ammonium metabolism, has a direct effect on the synthesis of nitrate reductase in this tissue.